2022
DOI: 10.1007/s00432-022-04337-y
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine reader YTHDF3 contributes to the aerobic glycolysis of osteosarcoma through stabilizing PGK1 stability

Abstract: N 6 -methyladenosine (m 6 A) modi cation is pivotal transcripts chemical modi cation of eukaryotic, which has been identi ed to play critical roles on tumor metabolic reprogramming. However, the functions of m 6 A reading protein YTH N 6 -methyladenosine RNA binding protein 3 (YTHDF3) in osteosarcoma is still unclear. This research planed to investigate the bio-functions and mechanism in osteosarcoma tumorigenesis. Results indicated that YTHDF3 up-regulated in the osteosarcoma tissue samples and cells, and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“… 261 In PDAC, YTHDF3-mediated destabilization of lncRNA DICER1-AS1 contributes to enhancing expression of glycolytic genes like LDHA, HK2, PGK1, and SLC2A1, 262 while YTHDF3 targeted m6A-modified PGK1 mRNA to exert a stabilizing role in OS. 263 IGF2BP1 was highly expressed in GC tissue and associated with poor prognosis for GC patients. IGF2BP1 promoted the migration and aerobic glycolysis of GC cells via directly interacting with c-MYC mRNA to stabilize it.…”
Section: Rna Modifications and Cellular Metabolismmentioning
confidence: 95%
“… 261 In PDAC, YTHDF3-mediated destabilization of lncRNA DICER1-AS1 contributes to enhancing expression of glycolytic genes like LDHA, HK2, PGK1, and SLC2A1, 262 while YTHDF3 targeted m6A-modified PGK1 mRNA to exert a stabilizing role in OS. 263 IGF2BP1 was highly expressed in GC tissue and associated with poor prognosis for GC patients. IGF2BP1 promoted the migration and aerobic glycolysis of GC cells via directly interacting with c-MYC mRNA to stabilize it.…”
Section: Rna Modifications and Cellular Metabolismmentioning
confidence: 95%
“…Besides METTL3, KIAA1429, YTHDF3, METTL16, WTAP, RBM15 and ALKBH5 are identified to regulate OS progression [ 15 , 181 , 185 , 187 , 192 , 201 ]. It is reported that KIAA1429 knockdown decreases the activity of JAK2/STAT3 signal to decreased cell proliferation, migration, and invasion of OS, which can be rescued by JAK2/STAT3 stimulator colivelin [ 188 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…And KIAA1429 can also act as a crucial gene to regulate Ewing sarcoma progression after CRISPR-Cas9 knockout [ 187 ]. Moreover, researchers found that aerobic glycolysis is essential to make sure OS cells obtain metabolic survival advantage compared with other cells [ 192 ]. Yang et al have proved that circ-CTNNB1 interacted with RBM15 drives aerobic glycolysis and OS progression by elevating key aerobic glycolysis genes expression, such as PGK1 [ 185 ].…”
Section: M6a and Skeletal System Diseasementioning
confidence: 99%
“…The exact pathogenic mechanisms of osteosarcoma remain largely unclear. It is currently believed to be associated with abnormal expression of certain genes, tumor microenvironment changes, glycolysis and other mechanisms ( Lilienthal & Herold, 2020 ; Liu et al, 2023 ). For example, inactivation of tumor suppressor genes like P53, and overexpression of oncogenes such as c-myc and c-fos can promote the initiation and progression of osteosarcoma ( Li et al, 2021 ; Han et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%